Proceedings of the 13th International Conference on Human Computer Interaction With Mobile Devices and Services 2011
DOI: 10.1145/2037373.2037385
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mobile web and mobile search use in today's dynamic mobile landscape

Abstract: The term mobile Web is changing. Mobile is traditionally associated with on-the-move, portable and dynamic. However, with the advent of smartphones, an increasing number of users are accessing the mobile Internet via their phone while in more stationary and familiar settings, like at home or at work. This shift in the meaning of mobile is having a significant effect on mobile Web behavior. Designing great mobile Web experiences requires a deeper understanding of the information needs, behaviors and underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 22 publications
5
69
0
1
Order By: Relevance
“…In our study, many of the information activities that took place in a car were precipitated by the proximity of the individuals or the just-in-time information needs that arose enroute to a destination, e.g., finding directions, or business hours, etc. The data we gathered about where our participants conducted their information activities confirmed that a significant amount of mobile IB occurs in non-mobile settings, such as at home or in the workplace (Church & Oliver, 2011;Nylander et al, 2009). We also observed that there were some locations, namely outside or public spaces, where social and non-social information activities occurred on par.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In our study, many of the information activities that took place in a car were precipitated by the proximity of the individuals or the just-in-time information needs that arose enroute to a destination, e.g., finding directions, or business hours, etc. The data we gathered about where our participants conducted their information activities confirmed that a significant amount of mobile IB occurs in non-mobile settings, such as at home or in the workplace (Church & Oliver, 2011;Nylander et al, 2009). We also observed that there were some locations, namely outside or public spaces, where social and non-social information activities occurred on par.…”
Section: Discussionmentioning
confidence: 67%
“…In a recent study of "just-in-time" information behaviors, 27% and 41% of those sampled indicated they used their mobile phones to settle an argument or coordinate a social gathering, respectively, within the past month (Rainie & Fox, 2012). Further, mobile search is often conducted in the presence of others (Church & Oliver, 2011;Amin, Setlur, Xi, Hayashi & Hong, 2009;Teevan, Karlson, Amini, Brush & Krumm, 2011), and searches may be socially motivated (Rahmati & Zhong, 2012) or prompted by conversations (Church & Smyth, 2009;Sohn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We argue that this group should be defined as 'distant learners' not just 'distance' learners. These learners transcend stationary environments [17] and demonstrate more mobility in their study routine. Data from the 2016 survey indicates that that distant learners comprise about a quarter of the undergraduate distance learning students surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Church and Oliver (2011) suggested that limitations in screen size and the type of interactions and input that mobile devices can support play an important role in shaping the way that mobile users use mobile search engines. Kamvar and Baluja (2006) found out that Google's PDA logs related to searches originating on PDAlike devices with sophisticated input capabilities.…”
Section: Research On the Mobile Search Contextmentioning
confidence: 99%